Two Case Studies on Electronic Distribution of Government Securities: The U.S. Treasury Direct System and The Philippine Expanded Small Investors Program - Glaesnner, Thomas G.; Kantur, Zeynep (World Bank, Washington, D.C., 2013)
The case study on the U.S. Treasury Direct examines the evolution of the electronic distribution systems for marketable and nonmarketable government securities, the main objectives, and the basic legal infrastructure and the preconditions enabling the system. The U.S. experience highlights that the enabling environment and infrastructure (for example, in terms of information databases such as Pay.Gov) make a large difference in terms of both the security and convenience that customers can expect in the use of the system. The system also achieved important cost savings for the Bureau of the Public Debt. The case study on the Small Investors Program of the Philippines looks at a program that the Philippine government has been experimenting with to sell its securities directly to retail investors over the Internet. The recently revised version of the program-called the Expanded Small Investors Program-aims to increase access to government securities and distribute them more widely, develop better savings products, and enhance competition in the primary markets for these securities. The authors analyze whether the program's main goals can be achieved while mitigating the risks. Their analysis suggests that there are good reasons to believe that the new program will succeed. Still, regular and responsive assessments and adjustments will be required as the program moves forward.